Battery energy management strategies for UK firm frequency response services and energy arbitrage. Issue 17 (26th April 2019) - Gundogdu, Burcu; Gladwin, Daniel; Stone, David
Abstract : Due to the increasing renewable penetration, there is potential for larger and faster grid frequency fluctuations increasing the risk of system instability. The National Grid Electricity Transmission, primary electricity transmission network operator in the UK, has introduced various frequency response services that are developed to provide a real‐time response to deviations in the grid frequency. A battery energy storage system is a suitable choice for delivering such services. Here, a control algorithm is presented which generates a charge/discharge power output with respect to deviations in the grid frequency and the required specifications. Using the real UK electricity prices, an arbitrage control algorithm has been also developed to deliver different types of grid balancing services, while scheduling throughout the day for energy arbitrage. Simulation results show that the proposed algorithm delivers both dynamic and non‐dynamic firm frequency response and also enhanced frequency response to specifications, while generating arbitrage revenue in the balancing market. Simulation results on a 1 MW/1 MWh lithium‐titanate BESS are provided to verify the proposed algorithm based on the control of an experimentally validated battery model.